Chemotaxonomic evaluation of wild lupine ecotypes northeast Argentina. - Merino, E. F.; Planchuelo, A. M. (1994)
Abstract.
Keywords: Lupinus; wild plants; Argentina; chemotaxonomy; thin layer chromatography; identification; alkaloids; metabolites; Argentiina; Etelä-Amerikka; Argentina; Sydamerika